2023
DOI: 10.21203/rs.3.rs-2951869/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinguishable Shot-term Effects of Tea and Water Drinking on Human Saliva Redox

Abstract: Food consumption can alter the biochemistry and redox status of human saliva, and the serving temperature of food may also play a role. The study aimed to explore the immediate (3 min) and delayed (30 min) effects of hot tea (57±0.5℃) ingestion and cold tea (8±0.5℃) ingestion on the salivary flow rate and salivary redox-relevant attributes. The saliva was collected from 20 healthy adults before, 3-min after and 30-min after the tea ingestion. The hot or cold deionised water at the same temperatures were used a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…23 The in vitro cellprotective activities of black tea nanoparticles, together with the co-existence of polyphenols and polysaccharides in the particles, show good potential in regulating intestinal barrier function and mucosal immunity in vivo. We have shown that the ingestion of black tea infusion immediately increased the salivary thiol (SH) and malondialdehyde (MDA) contents while reducing salivary uric acid (UA), 24 demonstrating the direct influences of tea infusion on oral mucosal cells. The black tea NPs aggregate under the acidic pH conditions of the stomach to form agglomerates and become more resistance to gastric digestion.…”
Section: Introductionmentioning
confidence: 98%
“…23 The in vitro cellprotective activities of black tea nanoparticles, together with the co-existence of polyphenols and polysaccharides in the particles, show good potential in regulating intestinal barrier function and mucosal immunity in vivo. We have shown that the ingestion of black tea infusion immediately increased the salivary thiol (SH) and malondialdehyde (MDA) contents while reducing salivary uric acid (UA), 24 demonstrating the direct influences of tea infusion on oral mucosal cells. The black tea NPs aggregate under the acidic pH conditions of the stomach to form agglomerates and become more resistance to gastric digestion.…”
Section: Introductionmentioning
confidence: 98%